Peran Fintech, Literasi Keuangan dan Inklusi Keuangan terhadap Kinerja UMKM di Kota Makassar - Rusdi; Nur Ikhsan, Muhammad; Syaharuddin, Syaharuddin (Study of Scientific and Behavioral Management, 2023)
The third national survey of financial literacy and inclusion (SNLIK) conducted by the financial services authority (OJK) in 2019 showed that the financial literacy index had increased by 8.33% compared to the previous SNLIK in 2016 and similarly the financial inclusion index had also increased. amounting to 8.39% from before. The rapid development of technology in the financial services sector also requires Indonesian people to be able to adapt. Thus, this research aims to determine the effect of financial literacy on financial inclusion with financial technology as an intervening variable in MSMEs in the city of Makassar. This research uses primary data and secondary data. The sampling technique in this research was using a probability sampling technique, so the number of samples in this research was 348 respondents. The data analysis technique in this research is using Structural Equation Modeling (SEM) using SmartPLS version 3.0 for Windows. The results of this research show that financial literacy has a positive effect on financial inclusion, financial literacy has a positive effect on financial technology, financial technology has a positive effect on financial inclusion, and financial literacy has a positive effect on financial inclusion through financial technology.